Rapid detection of mpox virus using recombinase aided amplification assay - Cui, Xiaohu; Du, Bing; Feng, Junxia; Feng, Yanling; Cui, Jinghua; Yan, Chao; Zhao, Hanqing; Gan, Lin; Fan, Zheng; Fu, Tongtong; Xu, Ziying; Zhang, Rui; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
A recent, unprecedented outbreak of human monkeypox virus infection has led to cases in non-African nations, and the number of confirmed or suspected cases outside of Africa has exceeded 1,000 within 5 weeks. Monkeypox may pose a double threat to public health in the context of the ongoing COVID-19 pandemic. It is difficult to distinguish monkeypox virus infection from other diseases in the early stages, and patients are contagious from the onset of nonspecific symptoms; therefore, it is crucial to develop rapid and specific diagnostic methods. The diagnosis of monkeypox relies on real-time polymerase chain reaction, a time-consuming method that requires a highly sophisticated thermal cycler, which makes it unsuitable for widespread use in underdeveloped areas, where the outbreak is still severe. In this study, we developed a recombinase-aided amplification assay (RAA) assay that can detect monkeypox virus within 5–10 minutes. The conserved regions of the A27L gene and F3L genes were selected as targets, as they amplify well from different monkeypox virus clades with no cross-reaction from other pathogens. The sensitivity of this RAA assay is 10 copies/reaction for the A27L gene and 102 copies/reaction for the F3L gene. When applied to simulated clinical samples, both targets showed 100% specificity, and the detection limits were consistent with the sensitivity results. In summary, the RAA monkeypox assay described here exhibits rapid detection, high sensitivity and specificity, and low operational difficulty, making it suitable for monkeypox virus detection in less developed countries and regions.